Escola sem Partido: ideologia e discurso - Toniol, Lucas Cardoso (2022)
In the past few years, the self-styled No Party School Movement (MESP) and their discourses have risen throughout the Brazilian scene. It is understood that the MESP has the potential to cause drastic and at the same time retrograde changes in Brazilian education, especially over the school and in the way it relates itself with the students. Hence, to comprehend the historical construction of the MESP as a discourse, the concepts on which it is based and the types of subjects it seeks to produce and silence, configure an important topic of study in contemporary times. The research developed took the discourses supported by MESP as object of analysis. The analysis undertaken was supported by Michel Foucault's contributions regarding his studies on the production of truths and discourse. In addition, a study was developed on the appropriation and meaningfulness adopted by MESP regarding the concept of ideology, one of the pillars of the Movement, as well as its self-denomination as a social movement. The results provide a broad understanding of MESP as inserted in a neoconservative and neoliberal discursive field, defending an antidemocratic and excluding education project. Consequently, it points to the effects of MESP on teaching subjectivities in terms of control, repression and the construction of the other as a threat.